(untitled) (PJDOL, 2023)
The research, which was taken into consideration, focused on assessing the effectiveness of vocabulary building through Read-Aloud Strategy for Primary level students. The main objective of the study was intended to identify the influence of read-aloud strategy on vocabulary building which is a key to other skills like reading comprehension and speaking skills and also to identify the effect of read-aloud strategy on the overall vocabulary development of the students of primary level.